Borewell Management, Deaths Of Children- A Case Study In India (Dangerous Than A Whole In Heart) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Imagine that suppose your children fell into a bore well nearby your home place how do you feel a feeling came to my mind.  When I go home I saw news in the Television Channel one boy fell in the bore well.  From the past 10 years I am hearing this news in TV channels.  99% people also I found dead while I thought that why it is happening I found a problem which is the starting point of my research.